2014
DOI: 10.2522/ptj.20130308
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Self-efficacy and Participation in Community-Dwelling Manual Wheelchair Users Aged 50 Years or Older

Abstract: Self-efficacy directly and indirectly influences the participation frequency in community-dwelling manual wheelchair users aged 50 years or older. Development of interventions to address low self-efficacy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…The LSA has been characterized as a participation measure in the literature 13,27,28 and could fulfill a need for outcome measures appropriate for persons with SCI regardless of their means of mobility. 29 Life wheeled mobility, either manual (LSA = 46.99) 16 or power (LSA = 33), 14 but smaller than that reported for a population-based study of persons aged 15 to 90 years (LSA = 98.3). 30 Despite the younger age of our sample, their LSA scores were comparable to the average reported for community-dwelling older adults with a mean age of 75 years (64.1 ± 24.9).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The LSA has been characterized as a participation measure in the literature 13,27,28 and could fulfill a need for outcome measures appropriate for persons with SCI regardless of their means of mobility. 29 Life wheeled mobility, either manual (LSA = 46.99) 16 or power (LSA = 33), 14 but smaller than that reported for a population-based study of persons aged 15 to 90 years (LSA = 98.3). 30 Despite the younger age of our sample, their LSA scores were comparable to the average reported for community-dwelling older adults with a mean age of 75 years (64.1 ± 24.9).…”
Section: Resultsmentioning
confidence: 72%
“…[11][12][13][14] Persons with SCI are certainly at risk for mobility disability. Although the LSA has been examined in populations that included persons with SCI, 15,16 to our knowledge no investigations have examined the LSA in a population limited to SCI. Such studies are important to ensure the appropriateness of outcome tool application.…”
mentioning
confidence: 99%
“…Specifically, we now know that: there is a high prevalence of low wheelchair confidence among adult manual wheelchair users; 16 wheelchair confidence influences life-space mobility 17 and participation 18,19 among community-dwelling manual wheelchair users; wheelchair confidence is a modifiable barrier to wheelchair use among both older adults 20 and occupational therapy students; 21 and there is a discordance between wheelchair confidence and wheelchair skill among adult manual wheelchair users. 16 These findings are of particular significance given that wheelchairs are prescribed to improve mobility and enhance one's ability to participate in their chosen daily activities, important rehabilitation outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence using Classical Test Theory methods indicates that the WheelCon measurements are both reliable and valid in manual wheelchair-users. 2 Furthermore, research using the WheelCon has shown that lower self-efficacy is associated with lower levels of participation frequency 3,4 and life-space mobility 5 in wheelchair-users aged 50 and older.…”
mentioning
confidence: 99%
“…Despite foundational research supporting the WheelCon's measurement properties, and the scale's effective use in research and clinical settings, [2][3][4][5][6][7][8][9] further evaluation of the WheelCon's measurement properties using contemporary measurement methods (i.e., Rasch analyses) may address current limitations with the existing scale. For example, during the development of the WheelCon, 1 items were created that inquire about beliefs pertaining to both physical (e.g.…”
mentioning
confidence: 99%